The concept of biophotonic signaling in the human body and brain: rationale, problems and directions - Nevoit, Ganna; Poderiene, Kristina; Potyazhenko, Maksim; Mintser, Ozar; Jarusevicius, Gediminas; Vainoras, Alfonsas (Frontiers in Systems Neuroscience, 2025)
This perspective piece presents the concept of the role and mechanisms of cells’ electromagnetic communication. These data deepen the scientific understanding of the fundamental aspects of the phenomenon of human life. A promising model of biophoton signaling as a scientific tool for further developing of biophotonics of the human body is substantiated.